2020
DOI: 10.1097/yct.0000000000000731
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy in Refractory Obsessive-Compulsive Disorder

Abstract: Electroconvulsive therapy (ECT) is a treatment of undisputed efficacy for severe and treatment-resistant psychiatric disorders. Notwithstanding extensive data on efficacy and safety, it is significantly underused, corresponding to one of the most stigmatized approaches in psychiatry. The list of problems for which ECT is potentially effective does not include obsessive-compulsive disorder (OCD), resulting in only a few available case reports in the literature in which OCD is the target of this specific therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…In our study, ECT was effective in the treatment of OCD without comorbid psychiatric disorders in both short-and mid-term evaluations. Some studies reported the data of patients with OCD who responded positively to ECT (Bülbül et al, 2013;Martins-Correia et al, 2021;Raveendranathan et al, 2012). Khanna et al reported the short-term anti-obsessional ECT outcomes in nine OCD cases (Khanna et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, ECT was effective in the treatment of OCD without comorbid psychiatric disorders in both short-and mid-term evaluations. Some studies reported the data of patients with OCD who responded positively to ECT (Bülbül et al, 2013;Martins-Correia et al, 2021;Raveendranathan et al, 2012). Khanna et al reported the short-term anti-obsessional ECT outcomes in nine OCD cases (Khanna et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Bülbül et.al concluded ECT for patients with a depressive episode of bipolar disorder and concurrent OCD and reported that both depression and OCD symptoms were successfully treated with ECT (Bülbül et al, 2013). In a study executed by Martins-Correia et.al, ECT was administered for a patient with refractory OCD, and the patient's clinical response and functional improvement were significant (Martins-Correia et al, 2021). Some other case reports also have demonstrated the positive effect of ECT on severe OCD patients (Hanisch et al, 2009;Loi & Bonwick, 2010;Tomruk et al, 2010) Because of the fear of neurological side effects, ECT for treatment of OCD was for decades a controversial treatment for treating OCD, but the patient's acceptance of this treatment has recently increased because the studies support the idea that the benefits of ECT outweigh the disadvantages (Moksnes et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this, ECT has a certain effect on OCD patients, but it has a less significant effect on refractory patients. The use of ECT has also been associated with significant improvements in refractory OCD in many cases (24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Due to this, ECT has a certain effect on OCD patients, but it has a less significant effect on refractory patients. The use of ECT has also been associated with significant improvements in refractory OCD in many cases ( 24 31 ). A small prospective study also found that ECT had an anti-obsessional effect ( 32 ).…”
Section: Discussionmentioning
confidence: 99%